Suppressing tawny crazy ant (Nylanderia fulva) by RNAi technology. (28th June 2018) - Meng, Jia; Lei, Jiaxin; Davitt, Andrew; Holt, Jocelyn R.; Huang, Jian; Gold, Roger; Vargo, Edward L.; Tarone, Aaron M.; Zhu‐Salzman, Keyan
Abstract: The tawny crazy ant ( Nylanderia fulva ) is a new invasive pest in the United States. At present, its management mainly relies on the use of synthetic insecticides, which are generally ineffective at producing lasting control of the pest, necessitating alternative environmentally friendly measures. In this study, we evaluated the feasibility of gene silencing to control this ant species. Six housekeeping genes encoding actin ( NfActin ), coatomer subunit β (NfCOPβ ), arginine kinase ( NfArgK ), and V‐type proton ATPase subunits A ( NfvATPaseA ), B ( NfvATPaseB ) and E ( NfvATPaseE ) were cloned. Phylogenetic analysis revealed high sequence similarity to homologs from other ant species, particularly the Florida carpenter ant ( Camponotus floridanus ). To silence these genes, vector L4440 was used to generate six specific RNAi constructs for bacterial expression. Heat‐inactivated, dsRNA‐expressing Escherichia coli were incorporated into artificial diet. Worker ants exhibited reduced endogenous gene expression after feeding on such diet for 9 d. However, only ingestion of dsRNAs of NfCOPβ (a gene involved in protein trafficking) and NfArgK (a cellular energy reserve regulatory gene in invertebrates) caused modest but significantly higher ant mortality than the control. These results suggest that bacterially expressed dsRNA can be orally delivered to ant cells as a mean to target its vulnerabilities. Improved efficacy is necessary for the RNAi‐based approach to be useful in tawny crazy ant management.